Smart 3D-printed facades: a review of innovations, materials, and sustainable performance - Dan-Radu Baraboi; Luminița Maria Scutaru; George Dragomir; Alin Ionuț Brezeanu; Răzvan Calotă; Mihaela Pavel; Gabriel Năstase (Frontiers in Sustainable Cities, 2025)
The construction industry faces increasing pressure to enhance energy efficiency, improve occupant comfort, and promote environmental sustainability. Smart 3D-printed facades represent a promising avenue for addressing these challenges, offering the potential for innovative architectural designs with enhanced performance characteristics. This paper is a narrative review examining the landscape of smart 3D-printed facade research between 2015 and 2025, analysing 76 relevant publications. There are significant advancements in material science, 3D printing techniques, and the integration of smart technologies into facade design. These developments demonstrate a notable capacity for improved energy performance and design flexibility. Specifically, 3D printing enables the creation of complex facade geometries, providing unprecedented design freedom and functional integration. The selection of sustainable and high-performance materials is crucial for optimizing energy efficiency, durability, and environmental impact. Furthermore, the integration of sensors, actuators, and AI-driven control systems allows for the creation of responsive facades that can dynamically adapt to environmental conditions and occupant needs. Critical challenges persist, including concerns regarding long-term durability, cost-effectiveness, scalability for large-scale applications, and the establishment of standardized testing and certification procedures. Future research should prioritize comprehensive lifecycle assessments to quantify environmental impacts and focus on developing robust material performance models under diverse climatic conditions. This will pave the way for the widespread adoption of this transformative technology in the built environment.